2009
DOI: 10.1002/cbic.200800411
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Physiological and Toxic Conformations in Aβ42 Aggregates

Abstract: Aggregation of the 42-residue amyloid beta-protein (Abeta42) plays a crucial role in the pathogenesis of Alzheimer's disease (AD). Despite numerous structural studies on Abeta aggregates, the relationship between tertiary structure and toxicity remains unclear. Our proline scanning and solid-state NMR studies suggested that aggregates both of wild-type Abeta42 and of E22K-Abeta42 (one of the mutants related to cerebral amyloid angiopathy) contain two conformers: a major one with a turn at positions 25 and 26, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(139 citation statements)
references
References 47 publications
(113 reference statements)
11
128
0
Order By: Relevance
“…By using this method, we successfully decoupled the aggregation from the HDX process. Importantly, we extracted kinetic information on the Aβ 42 aggregation at 25°C, indicating that the middle region of the Aβ 42 peptide (i.e., [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] was the "seeding" region in aggregation, followed by the C-terminus hydrophobic region (i.e., [36][37][38][39][40][41][42] and then the N-terminus hydrophilic region (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Finally, we showed that this approach allowed us to examine directly the factors that affect the oligomerization of Aβ 42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using this method, we successfully decoupled the aggregation from the HDX process. Importantly, we extracted kinetic information on the Aβ 42 aggregation at 25°C, indicating that the middle region of the Aβ 42 peptide (i.e., [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] was the "seeding" region in aggregation, followed by the C-terminus hydrophobic region (i.e., [36][37][38][39][40][41][42] and then the N-terminus hydrophilic region (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Finally, we showed that this approach allowed us to examine directly the factors that affect the oligomerization of Aβ 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Upon pulsed HDX of the preformed fibrils we observed both the peptides formed by pepsin digestion (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and the undigested Aβ 42 . The peptides and the full Aβ 42 are similarly protected (89 ± 1% for the undigested Aβ 42 and 85 ± 1%, 84 ± 1%, and 91 ± 2% for 1-19, 20-35 and 36-42, respectively), consistent with the peptides' being proteolytic fragments from the amyloid fibrils.…”
Section: Application Of Finke-watzky Modeling and Statistical Evaluatmentioning
confidence: 99%
See 1 more Smart Citation
“…Research effort has been mainly focused on the most abundant forms Aβ , which comprises 40 amino acids, and the longer Aβ , which is C-terminally extended by two hydrophobic residues and has been found to be more aggregation-prone (83). Nonetheless, it has recently been discovered that the co-occurrence of peptides varying in length can affect the neurotoxic and aggregation potential of the total Aβ pool (84)(85)(86)(87)(88)(89)(90). It has also been recognized that particularly small aggregated forms of Aβ are potently toxic, rather than the mature amyloid fibrils as observed in the brains of AD patients.…”
Section: The Amyloid-beta Peptide: the Primary Driver Of Ad Pathogenesismentioning
confidence: 99%
“…1.4 Various forms of Aβ co-exist and co-deposit in amyloid fibrils and plaques (99,203). It has become clear that biologically relevant mixtures of Aβ alloforms behave in a more complex manner in vitro than anticipated from their behaviour in isolation, in terms of aggregation properties and toxicity (84,85,(88)(89)(90). For example, Aβ and Aβ 1-40 exerted little toxicity in isolation, but were highly toxic to a neuroblastoma cell line when tested in a mixture, whereas addition of Aβ to Aβ 1-42 had a cytoprotective effect (90).…”
Section: The In Vivo Aβ Peptide Pool: a Cocktail Of Different Interacmentioning
confidence: 99%